Do Norwegian Firms Form Exptrapolative Expectations? - Ingvild Svendsen (Statistics Norway, Research Department, 1994)
The hypothesis of extrapolative expectations is tested directly using Norwegian microeconomic data on firms' expectations of the prices of own products in domestic and export markets and expectations of demand for own products in domestic and export markets. The data, which are categorical, are taken from a survey of firms in manufacturing and mining. Different versions of extrapolative models are discussed, i.e. the general extrapolative model, the pure adaptive scheme and the error-learning model. The data are analyzed by means of different measures of association in cross-tables and loglinear probability models. Because of the sample size and the distribution of observations through out the table, statistical conclusions cannot be drawn for the hypothesis of adaptive expectations. For this version of extrapolative expectations, only descriptive measures are provided. Our empirical results support a general version of extrapolative expectations. The restrictions on the lag structure which take us from the general version to the model of adaptive expectations do, when confronted with our data, seem to be too restrictive.
Keywords: C21; C42; D84; 330; Extrapolative Expectations; Microeconomic Data; Tendency Surveys